Amino acid analyses of R and CK chondrites. (13th March 2015) - Burton, Aaron S.; McLain, Hannah; Glavin, Daniel P.; Elsila, Jamie E.; Davidson, Jemma; Miller, Kelly E.; Andronikov, Alexander V.; Lauretta, Dante; Dworkin, Jason P.
Abstract: Exogenous delivery of amino acids and other organic molecules to planetary surfaces may have played an important role in the origins of life on Earth and other solar system bodies. Previous studies have revealed the presence of indigenous amino acids in a wide range of carbon‐rich meteorites, with the abundances and structural distributions differing significantly depending on parent body mineralogy and alteration conditions. Here we report on the amino acid abundances of seven type 3–6 CK chondrites and two Rumuruti (R) chondrites. Amino acid measurements were made on hot water extracts from these meteorites by ultrahigh‐performance liquid chromatography with fluorescence detection and time‐of‐flight mass spectrometry. Of the nine meteorites analyzed, four were depleted in amino acids, and one had experienced significant amino acid contamination by terrestrial biology. The remaining four, comprised of two R and two CK chondrites, contained low levels of amino acids that were predominantly the straight chain, amino‐terminal ( n ‐ω‐amino) acids β‐alanine, and γ‐amino‐ n ‐butyric acid. This amino acid distribution is similar to what we reported previously for thermally altered ureilites and CV and CO chondrites, and these n ‐ω‐amino acids appear to be indigenous to the meteorites and not the result of terrestrial contamination. The amino acids may have been formed by Fischer–Tropsch‐type reactions, although this hypothesis needs further testing.